From the First Renaissance to the Second: The Historical and Legal Basis for the Sultanate - Salimi, Abdulrahman al- (2020)
Organisateur: Georgia State University
Keywords: Vie politique – Oman – 1970-2020

Ibāḍism East of Mesopotamia: Early Islamic Iran, Central Asia and India - Salimi, Abdulrahman al- (Dar al-Farabi : Klaus Schwarz Verlag, 2016)
Keywords: Ibadisme – Asie centrale

The research on Medieval Ibadism in Oman : historiographical tendencies and documentary resources - Salimi, Abdulrahman al- (2011)

Early Ibāḍī Creed in the 2nd/8th Century: A Study of Wā'il Bin Ayyūb's “Nasab Al Islam” (“the Lineage of Islam”) - Salimi, Abdulrahman al- (The Muslim World, 2015)
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/muwo.12088
Keywords: Foi – Traité – 8e siècle

The Omani siyar as a literary genre and its role in the political evolution and doctrinal development of Eastern Ibadism, with special reference to the epistles of Khwarizm, Khurasan and Mansura - Salimi, Abdulrahman al- (Durham University, 2001)

The political organization of Oman from the Second Imamate period to the Yaʻrūba: rereading Omani internal sources - Salimi, Abdulrahman al- (2013)

Oman and Ibadism from a Religious Regional Perspective - Salimi, Abdulrahman al- (Istituto Lombardo - Accademia di Scienze e Lettere - Incontri di Studio, 2017)
Questo paper affronta il tema dell’identità Omanita e l’ideologico religioso Islamico Ibadita. Fra gli elementi principali che caratterizzano l’Oman, si possono considerare: 1. La sua particolare configurazione geografica. 2. La sua popolazione multi-culturale e multi-religiosa sin da epoche antichissime e precedent l’Islam stesso. 3. La dottrina Islamica Ibadita. Conseguentemente, in primo luogo l’Autore si sofferma sulle particolari connotazioni geografiche dell’Oman e suoi molteplici ‘paesaggi’, i quali hanno indubbiamnete avuto un profondo impatto sugli habitat umani e la loro organizzazione all’interno delle diverse nicchie ecologiche del Paese, risalendo a secoli se non a millenni or sono. Riguardo a quest’ultimo aspetto, una delle principali connotazioni è stata quella del tribalismo e le sue complementarietà all’interno di una cornice che, in Oman, è sempre stata caratterizzata da multi-culturalità e multi-religiosità. Quindi, con l’avvento dell’Islam, un nuovo fattore si è imposto sulla scena storica omanita: l’Ibadismo e le sue dinamiche. Dopo un breve schema storico e in ampia parte riferendosi al paper precedente, il discorso puntualizza i principî base dell’Ibadismo e della sua evoluzione nel tempo, il ruolo giocato in Oman nel corso dei secoli, il suo impatto sulla società locale e il modello politico-istituzionale che esso ha contribuito a forgiare e modellare. Si tratta di una eredità culturale tramandata nei secoli fino ad oggi. Infine, l’Autore dà un rapido ma chiaro affresco dell’Ibadismo e del suo ideologico religioso oggi, il rapporto fra questa ideologia religiosa e il concetto di Modernità tecnologica e sociale, Corano e principî guida religiosi di fronte alle diversità, la risposta Ibadita di fronte a un nuovo modello di società inter-religiosa e inter-etnica.

Qalhat-Hurmuz: Its Place in the History and Economy of the Western Indian Ocean in the Later Middle Ages - Salimi, Abdulrahman al- (Studi Magrebini, 2021)
Abstract This article aims at shedding light on the late medieval trading system in the western part of the Indian Ocean between the Gulf and the east coast of Africa, in order to offer new evidence on the so-called “Shirazi question”. I will dispute the alleged early tenth/eleventh century date of the (possibly fictitious) “Shirazi migration” to East Africa by examining the background of the socio-economic and political changes which took place between the tenth and the fifteenth century. The trade network in which Hormuz – including Qalhat – played an important part is well documented by a homogenous pottery assemblage, which combines finds from the Makran/Baluchistan coast, the Gulf, Hormuz-Qalhat, Tiwi and farther south with many places on and off the coast of East Africa. This is important for our suggestion that the Shirazi-legend should be placed in the Hormuz-Qalhat period between the twelfth and fifteenth centuries. A quantity analysis of the recorded sites between the Lamu region in the north and the Kilwa region in the south testifies to a constant rise of settlement activity or settlement expansion between the twelfth and fifteenth centuries, reaching a peak in the fourteenth century (43 out of 116 examined places) and the fifteenth century (53 out of 116 examined places). Taking these facts together, we shall turn again to the grey area between legend and historical fact.

Imārat Banī Makram fī ʿUmān - Salimi, Abdulrahman al- (نزوى: مجلة فصلية ثقافية, 2002)

The Wajīhids of Oman - Salimi, Abdulrahman al- (Proceedings of the Seminar for Arabian Studies, 2009)
The downfall of the first Omani imamate in 280/885 represented the beginning of clashes between Ibāḍī ideology and the emerging family dynasties in different Omani provinces. The dynastic rulers sought to abolish the imamate system in the country, which led to serious conflict between distinguished political families and Ibāḍī scholars. Perhaps Wajīhid's reign in the fourth/tenth century symbolizes this best. This important family's rule of the country brought about fundamental changes in the areas of politics and commerce, which in turn has occupied the interest of many historians and archaeologists. This paper focuses on the emergence of the Wajīhid, their relations with Omani Ibāḍīs, and the subsequent political and economical changes in Oman. Finally, the paper examines this development in relation to the centre of the caliphate in Baghdad, the Būyids and Qarmatians (Carmathians).
Keywords: Archéologie – Oman

The Sirah to the People of Khwarazm - Salimi, Abdulrahman al- (Ibāḍism East of Mesopotamia: Early Islamic Iran, Central Asia and India, 2016)
Keywords: Ibadisme – Asie centrale

Ishkāliyyat Tawthīq al-Shakhṣiyyāt al-ʿUmāniyya al-Mubakkira: Munīr b. al-Nayyir Unmūdhajan - Salimi, Abdulrahman al- (نزوى: مجلة فصلية ثقافية, 2005)

The Cosmology Argument in Early Ibadi Theology - Salimi, Abdulrahman al- (2010)

Jannāwunī, Abū Zakariyyāʾ al- - Salimi, Abdulrahman al- (Encyclopaedia of Islam, 2008)
Keywords: Biographies – Djebel Nefousa; Jannāwunī; Yaḥyā b. al-Khayr

The Sirah to the People of Khurasan - Salimi, Abdulrahman al- (Ibāḍism East of Mesopotamia: Early Islamic Iran, Central Asia and India, 2016)
Keywords: Ibadisme – Asie centrale

Early Islamic law in Basra in the 2nd/8th century: Aqwal Qatada b. Diʻama al-Sadusi - Salimi, Abdulrahman al- (Brill, 2018)
Keywords: Fiqh

Treatises on the Islamic firaq (Sects) and the Origin of Islamic kalām: Early Kufa-Baghdad Literature - Salimi, Abdulrahman al- (Studia Islamica, 2025)
Abstract This study examines two late 2nd/8th century books that have been edited and published recently: Abū Muḥammad ʿAbd Allāh b. Yazīd al-Fazārī (d. c.185/800)’s Kitāb al-Rudūd (The Book of Responses) and Ḍirār b. ʿAmr al-Ġaṭāfānī’s (d. c.200/810) Kitāb al-Taḥrīš (The Book of Provocation). Both texts shed light on the emergence of ʿilm al-kalām (scholastic theology) in early Islam and its relationship to books and treatises on the Islamic firaq (sects) – a relationship which until now has not been sufficiently examined. In comparing these two texts, we focus on the specific topics they share, the methodologies they use, and the technical terms they employ. We conclude that the emergence of ʿilm al-kalām, as well as the Islamic “contemplative disciplines” in general, occurred not primarily, as is often surmised, as a result of external Greek philosophical influence but rather as the result of a politico-theological debate that took place within Muslim communities. We also reconsider the nature of intellectual life during the early Abbasid period.
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle; Ġaṭāfānī; Ḍirār b. ʿAmr al-

Orientalism and relationships between Islam and The West - Salimi, Abdulrahman al- (Krakowskie Studia Międzynarodowe, 2009)
"Since the end of the Second World War, a dispute has continued amongst Muslims and Arabs regarding the character of Orientalism. The period during the Cold War played a principal role in the shaping of disparate views when some of the key Arab states leaned towards the former Soviet Union, while others aligned themselves with the United States and its allies. Such alignments resulted in distinctive orientations towards cultural studies that found expression in a ‘soft’ confrontation led by Islamists on one side and leftwing leaders on the other. In exploring these differences, it is important to begin by defining what is meant by Orientalism. To do this, one needs to examine the three main areas of scholarly focus in the last two hundred years: the editing of Arabic manuscripts, historical scholarship on Islam, and Islamic religious studies and its associated branches."(...)

Theology and heresiography in Early Islamic Oman: the epistle of Khalf b. Ziyad - Salimi, Abdulrahman al- (2023)

Taʿaddudiyyat al-ʿAwtabī wa-Tarjamatuhu aw Ishkāliyyāt Shakhṣiyyat al-ʿAwtabī al-Ṣuḥārī - Salimi, Abdulrahman al- (نزوى: مجلة فصلية ثقافية, 2000)
A discussion on al-ʿAwtabī’s name and genealogy. Sālimī reaches the conclusion that there were two persons with the name Salma b. Muslim al-ʿAwtabī, one with the Kunya Abū ‘l-Mundhir and the other with the Kunya Abū Ibrāhīm. See Mashriq, Ṣuḥārī, Abū ‘l-Mundhir Salāma (Salma) b. Muslim: K. Ansāb al-ʿArab.

Ibadism and Oman - Salimi, Abdulrahman al- (2015)

An Exaggeration of Qur’an by the Baghdadi Mu‘tazilite: Studying Abu Tahir al-Turaythithi - Salimi, Abdulrahman al- (Manuscripta Orientalia, 2014)
The objective of this paper is to shed the light to the series of manuscripts of the treatise al-Mutashabih fi al-Qur’an ( Ambiguous [ayat] in the Qur’an ) by Abu Tahir al-Turaythithi, Mu'tazilte scholar of Baghdad. The problem discussed is the exaggeration of the Qur’an which was the point of sharp theological debates. We know comparatively well the Mu'tazilte works produced in Basra while the work by Abu Tahir al-Turaythithi reflects comprehensively the school of Baghdad. The journey of the treatise through the Muslim world as presented by its manuscripts started from Central Asia, they appeared in Yemen and Oman and finally in one of the European libraries.
Keywords: Coran – Commentaires

al-Buʿd al-Tārīkhī li-Shurūḥāt al-Manẓūmāt al-ʿAqadiyya: al-Daʿā’im li-Ibn al-Naḍr al-Ibāḍī Unmūdhajan - Salimi, Abdulrahman al- (2003)
FMC 13 p.

On Studying the early historical sources: The Epistle of Khalf b. Ziyad al-Bahrani - Salimi, Abdulrahman al- (2022)

Ibadi Texts in Oman from the 3rd/9th Century - Salimi, Abdulrahman al- (Brill, 2021)
This volume contains twenty-three texts, most of which were written between the end of the 2nd/8th century and the end of the 3rd/9th century. The majority of them reflect the early stages of the development of the First Ibadi Imamate in 132/750 – established when the Omanis fully seceded from the central state in Baghdad until the Imamate was collapsed by the Abbasids in 280/893. The source value of these Ibadi texts for researchers and scholars specialised in Islamic studies far outweighs any importance they might attach to sectarian history per se. 1 The Epistle of Mūsā b. Abī Jābir سيرة موسى بن أبي جابر 2 Letter of Abū Mawdūd to Imam Ghassān b. ʿAbdallāh نصيحة أبي مودود للإمام غسّان بن عبد الله 3 Epistle of Abū Mawdūd Ḥabīb b. Ḥafṣ al-Hilālī to Imam Ghassān b. ʿAbdallāh سيرة أبي مودود حبيب بن حفص الهلالي إلى الإمام غسان بن عبد الله 4 Epistle of Munīr b. al-Nayyīr al-Riyāmī al-Jaʿlānī to Imam Ghassān b. ʿAbdallāh سيرة المنير بن النيّر الريامي الجعلاني إلى الإمام غسان بن عبدالله 5 Epistle of Abū Sufyān Maḥbūb b. al-Raḥīl to Imam al-Muhannāʾ b. Jayfar about Hārūn b. al-Yamān سيرة أبي سفيان محبوب بن الرحيل إلى الإمام المهناء بن جيفر بشأن هارون بن اليمان 6 Epistle of Abū Sufyān Maḥbūb b. al-Raḥīl to the People of Ḥaḍramawt about Hārūn b. al-Yamān سيرة أبي سفيان محبوب بن الرحيل إلى أهل حضرموت بشأن هارون بن اليمان 7 Epistle of Hārūn b. al-Yamān to Imam al-Muhannāʾ b. Jayfar about Abū Sufyān Maḥbūb b. al-Raḥīl سيرة هارون بن اليمان إلى الإمام المهناء بشأن أبي سفيان محبوب بن الرحيل 8 Letter from Hāshim b. Ghaylān al-Humaymī to Imam ʿAbd al-Malik b. Ḥumayd جواب مِن هاشم بن غيلان إلى الإمام عبد الملك بن حُمَيْد\سيرة 9 Epistle of Abū ʿAlī [Mūsā b. ʿAlī] to the shurāt سيرة لأبي علي للشراة 10 Letter from Hāshim b. Ghaylān al-Humaymī to Imam ʿAbd al-Malik b. Ḥumayd سيرة هاشم بن غيلان إلى الإمام عبد الملك بن حُمَيد 11 Letter from Mūsā b. ʿAlī to Imam ʿAbd al-Malik b. Ḥumayd سيرة موسى بن علي إلى الإمام عبد الملك بن حُمَيد 12 Letter from Mūsā b. ʿAlī [b. ʿAzra], Hāshim b. Ghaylān and the People of Izkī to Imam ʿAbd al-Malik b. Ḥumayd موسى بن عليّ و هاشم بن غيلان وأهل إزكي إلى الإمام عبد الملك بن حُمَيْد سيرة 13 Letter from Hāshim b. Ghaylān, Muḥammad b. Mūsā, al-Azhar b. ʿAlī, al-ʿAbbās b. al-Azhar, Mūsā b. Muḥammad and Saʿīd b. Jaʿfar to Imam ʿAbd al-Malik b. Ḥumayd سيرة من هاشم بن غيلان ومحمّد بن موسى والأزهر بن علي والعبّاس بن الأزهر ومحمّد ابني عليّ وسعيد بن جعفر إلى الإمام عبد الملك بن حُمَيد 14 Epistle of Imam al-Muhannāʾ b. Jayfar to Maʿādh b. Ḥarb سيرة الإمام المهناء بن جيفر إلى معاذ بن حرب 15 Letter from Imam al-Ṣalt b. Mālik and Muḥammad b. Maḥbūb to Aḥmad b. Sulaymān, the Imam of Ḥaḍramawt جواب من الإمام الصلت بن مالك ومحمّد بن محبوب إلى أحمد بن سليمان إمام\سيرة حضرموت 16 Epistle of Muḥammad b. Maḥbūb to the People of the Maghreb (North Africa) سيرة محمد بن محبوب لأهل المغرب 17 Epistle of Imam al-Ṣalt b. Mālik سيرة الإمام الصلت بن مالك 18 Epistle of Muḥammad b. Maḥbūb [b. al-Raḥīl] to Abū Ziyād Khalaf b. ʿAzra سيرة محمّد بن محبوب إلى أبي زياد خلف بن عزرة 19 Letter from Abū ʿAbdallāh Muḥammad b. Maḥbūb to Imam al-Ṣalt b. Mālik Regarding the People in Prison الصلت بن مالك في أهل السجن[الإمام]جواب مِن أبي عبدالله محمّد بن محبوب إلى 20 Epistle of Shaykh ʿAzzān b. al-Ṣaqr سيرة أبي معاوية عزّان بن الصقر 21 Epistle of Imam [Abū l-Yaqẓān] Muḥammad b. Aflaḥ رسالة الإمام محمد بن أفلح 22 Epistle of Abū l-Muʾthir al-Ṣalt b. Khamīs al-Kharūṣī سيرة أبي المؤثر الصلت بن خميس 23 Epistle of Abū l-Ḥasan ʿAlī b. Muḥammad al-Basyāwī Regarding Monotheism and the Imamate سيرة الشيخ أبي الحسن البسيوي
Keywords: Sources – Ibadisme

Themes of the Ibadi/Omani Siyar - Salimi, Abdulrahman al- (Journal of Semitic Studies, 2009)
Keywords: Prosopographie – Oman

min Maṣādir al-Tārīkh wa’l-Thaqāfa, al-Siyar al-ʿUmāniyya - Salimi, Abdulrahman al- (نزوى: مجلة فصلية ثقافية, 2000)
Sālimī’s article is based on the following sources: - A MS collection in three volumes in MNHC, dated 1299/1881, dedicated to al-Sayyid Barghash b. Saʿīd, Sultan of Zanzibar. (See Mashriq, Anonymous: Siyar al-ʿUlamā’ al-Ibāḍiyya al-Maḥbūbīyyīn). - A MS collection in one volume in Makt. al-Sālimī, dated 1120/1708, entitled K. al-Siyar. (See Mashriq, Anonymous: K. al-Siyar (2)). - A MS collection of three parts in one volume in the possession of Aḥm. b. Nāṣir al-Sayfī in Nizwà, dated 1141/1728. (See Mashriq, Anonymous: al-Siyar al-Ibāḍiyya). - Ibn Baraka: K. al-Taqyīd, a MS in Makt. al-Sālimī, dated 972/1564. - A microfilm in the library of Cambridge University (Or. 1405), entitled al-Siyar al-ʿUmāniyya. (see Mashriq, Anonymous: Hinds Xerox). MS collections, Sālimī has not seen: - A MS collection in the library of the former Imam Ghālib b. ʿAlī al-Hinā’ī in Dammam, Saudi Arabia. (See Mashriq, Anonymous: al-Siyar wa’l-Jawābāt). - MS in the library of the University of Lwów. (See Mashriq, Anonymous: al-Siyar al-ʿUmāniyya). Printed works that contain i.a. Siyar: - Khurāsiyyīnī, Saʿīd b. Aḥm.: Fawākih al-ʿUlūm fī Ṭāʿat al-Ḥayy al-Qayyūm. (See Khurāsiyyīnī). - Kāshif: (ed.) al-Siyar wa’l-Jawābāt li-ʿUlamā’ wa-A’immat ʿUmān. (See Mashriq, Kāshif). - Sālimī: Tuḥfat al-Aʿyān. - Baṭṭāshī, Sayf b. Ḥamūd: Itḥāf al-Aʿyān fī Tārīkh baʿḍ ʿUlamā’ ʿUmān (q.v.). The Omani Siyar are a kind of short theological and/or political memoranda of not more than 20 to 30 fos. that present a personal viewpoint on a certain subject. They can be seen as an archive of memoranda and correspondence on a variety of crises and subjects. The Omani Siyar contain: an opinion of a scholar on a certain subject or event; correspondence between parties in which they discuss a certain subject; writings or answers or exchange of opinions between scholars to explain a certain question, a kind of epistles we see especially during the period of the split into Rustāqiyya and Nizwāniyya parties; registration of events in a certain period, or sometimes writings on famous Imams, scholars and jurists, i.e. a kind of biographies. On the contrary, the Ibāḍīs of North Africa use the term Sīra in the sense of biography; a Sīra in the Omani sense of the word, they most often call Kitāb (letter). At a certain point in time, the term Sīra took on a different meaning with the Omani historians, for the first time, as far as we know, with Ibn Qayṣar in his Sīrat al-Imām Nāṣir b. Murshid al-Yaʿrabī (Imam 1043-1059/1624-1649), which is a biography. The compilation of epistles as a kind of literary genre probably began in the 11th/17th century, and all later Omani historians made use of the older Siyar in their works. The epistles in these compilations are not aranged chronologically nor according to subject and they contain also non-Omani epistles. With regard to the historical importance of the Omani Siyar, see for example Wilkinson 1976a, 1978b (see Anonymous: Jawhar al-Muqtaṣir) and 1981, Fārūq ʿUmar Fawzī 1979a, ʿUbaydlī in the introduction to his edition of Kashf al-Ghumma (1985), and Cook 1981 (to which Crone and Zimmermann 2001 can be added). A chronological arrangement of more than 126 epistles, with an indication of their subjects and explanatory remarks (pp. 10-36): I. First period: from the beginnings of the Islam until the collapse of the First Imamate in Oman (280/893-4): (i) The period of Medina and the Ṣaḥāba (6 epistles). (ii) The period after the murder of Caliph ʿUthmān b. ʿAffān (35-45/656-665) (7 epistles). (iii) The period of formation of Ibāḍī political, theological and juridical thought in al-Baṣra (18 epistles). (iv) Epistles composed during the reigns of the Imams Ghassān b. ʿAbdl. al-Fajḥī (192-207/808-823) and ʿAbd al-Malik b. Ḥumayyid al-ʿAlawī (208-226/823-841) (7 epistles). (v) Epistles composed during the reign of Imam al-Muhannā b. Jayfar al-Fajḥī (226-237/841-851) (4 epistles). (vi) Epistles composed during the reign of Imam al-Ṣalt b. Mālik al-Kharūṣī (237-272/851-886) and when Muḥ. b. Maḥbūb b. al-Raḥīl (d. 260/874) arrived in Oman (10 epistles). II. Second period: starting from the deposing of Imam al-Ṣalt b. Mālik (272/886) This period saw internal strife in Oman between Nizāriyya and Qaḥṭāniyya tribes and ideological differences of opinion on the rules of the Imamate between the Rusṭaq and the Nizwà parties, of which the former supported Imam al-Ṣalt b. Mālik while the latter took up a moderate position between the supporters of the Imam and his opponents. The first Imamate in Oman collapsed at the hands of Muḥ. b. Nūr/Būr, Abbaside governor of Bahrain. (i) Epistles of the Rusṭāq school (15 epistles). (ii) Epistles of the Nizwà school (5 epistles). (iii) Epistles of opponents of Imam al-Ṣalt b. Mālik (2 epistles). III. Third period: the Second Imamate in Oman (320-549/923-1154). (i) Epistles composed in the period between the reigns of the Imams Abū ‘l-Qāsim Saʿīd b. ʿAbdl. (320-328/931-940) and al-Khalīl b. Shādhān (407-425/1016-1033) (6 epistles). (ii) The period of liberation of Oman from foreign occupiers and of commercial expansion in the Indian Ocean and East Africa, as well as expansion of the Imamate into Ḥaḍramawt and Yemen (12 epistles, among which a compilation of three from Imam Rāshid b. Saʿīd). (iii) Epistles composed towards the end of the Second Imamate (19 epistles). IV. Fourth period: from the Nabāhina state (549-1043/1154-1624) to the Yaʿāriba state (1624-1741). (i) The period of the Nabāhina (10 epistles). (ii) The period of the Yaʿāriba (6 epistles, among which a compilation of four epistles of Imam Nāṣir b. Murshid to his governors). Nearly the same article in Nizwà, nr. 2 (July 1999) (http://www.nizwa.com/volume19/p62_78.html.). See Salmi 2001, chapt. 1 (pp. 1-45). See Salimi, Abdulrahman 2010a (pp. 124-160, a chronological arrangement of 140 epistles).

A comparison of modern religious education in Arabia: Oman and Yemen - Salimi, Abdulrahman al- (2011)
FMC 13 p.
Keywords: Enseignement – Oman

Early Ibāḍī Theological Arguments on Atoms and Accidents - Salimi, Abdulrahman al- (Arabic Sciences and Philosophy, 2013)
Le gros de la recherche orientaliste consacrée à la littérature théologique islamique a négligé les idées théologiques Ibāḍī à portée cosmologique, ce qui a conduit à une compréhension incomplète de la théologie islamique et à un manque considérable dans la recherche occidentale. L'omission de ce mouvement important de l'Islam est compréhensible étant donné que les textes Ibāḍī ne sont accessibles, publiés, diffusés et traduits que de façon très partielle. Cette étude vise donc à combler certaines de ces lacunes dans la recherche sur la première théologie islamique. Les objectifs de cet article sont de: 1) caractériser la littérature Ibāḍī classique portant sur la théorie atomiste de la substance et de l'accident; 2) examiner les textes d'auteurs Ibāḍī du iiie/ixe siècle dialoguant et discutant avec d'autres écoles théologiques islamiques, à savoir les Muʿtazilites pré-Bahshamiyya (Abū Hāshim al-Jubbāʾī, d. 321/933) et les Ashʿarites (Abū al-Ḥasan al-Ashʿarī, d. 324/936), en lien avec la théorie atomiste de la substance et de l'accident; 3) passer en revue le grand nombre d'opinions soutenues parmi les premiers théologiens Ibāḍī, et examiner les sources et les thèmes spécifiques susceptibles d'avoir influencé cette école de pensée diversifiée. Cet article cherche aussi à identifier des traits communs dans l'approche Ibāḍī durant la période de formation de la théologie islamique, et à explorer les voies grâce auxquelles ces premiers théologiens ont pu avoir accès à des thèmes cosmologiques antérieurs à l'Islam.

On the Significance of the Aqwal Qatada for Early Islamic Legal Thought - Salimi, Abdulrahman al- (2017)
The Aqw?l Qat?da (the Sayings/teachings of Qat?da) is a collection of writings on fiqh (jurisprudence) and ?ad?th (traditions) narrated by Qat?da b. Di'ama al-Sadusi (c.60-117/680-735) that has frequently attracted the interest of present-day scholars. In addition to these writings, the discovery of a number of previously unknown texts on Ib??? jurisprudence and early legal opinions in the Maghrib region by a non-Ib??? scholar from Ba?ra now raises important questions about early Ib??? history and the proper methods of recording information during Islam’s formative period during the first half of the 2nd /8th century. Although these texts have not yet been published, they are the subject of intense debate amongst modern scholars. Although the Aqw?l Qat?da was never incorporated into the legal literature of the Ib??iyyah in Oman, manuscripts of the Aqw?l Qat?da have repeatedly attracted particular interest among modern scholars as it raises questions concerning the early development of the Ib??? Ba?ran community. It is a unique document because it attests to the existence of a scholarly link between Sunn?s and Ib???s during the early development of Islamic law. The fact that the legal responses and traditions of Qat?da are part of an Ib??? collection, in which the traditions of J?bir bin Zayd (one of the founders of Ibadism) have been transmitted through ‘Amr b. Harim and ‘Amr b. D?n?r, proves that Ib??? lawyers of the first generations considered Qat?da to be a faithful upholder of J?bir's doctrine. This present study on the text is based on two recently discovered manuscripts. One of these is in the D?r al-Kutub al-Mi?riyyah in Cairo, while the other is in the al-B?r?niyyah Library (al-Khiz?nah al-B?r?niyyha) on the Tunisian island of Djerba. We shall look at both of them in detail. The texts display three important features, which will be the subject of analysis: 1) fiqh opinions commonly held during the early Islamic period in Ba?ra; 2) early approaches to the collection of Islamic religious traditions including ?ad?th of the Prophet and legal opinions of the early community 3) the development of Islamic jurisprudence during the first two centuries of the Islamic era.
Keywords: Fiqh

The Transformation of Religious Learning in Oman: Tradition and Modernity - Salimi, Abdulrahman al- (Journal of the Royal Asiatic Society, 2011)
The last fifty years mark a period of great change in the role of religious leadership and education in the Sultanate of Oman. The country moved from bifurcated leadership between an Imam and a Sultan to a single political authority. These decades also witnessed the modernisation of the state. These factors combined to reshape the place of religion and religious education in society. Whereas previously religious leaders had relative autonomy and more direct political influence, now they were brought under the auspices of the government with their focus circumscribed to religious matters. The structures and foci of religious education were then reshaped so that tradition provided a platform for progress and the more zealous ideologies emerging in the region could be held at bay. This has permitted Oman to modernise and engage with a global society in an amicable, non-sectarian, manner.
Keywords: Enseignement – Oman

On the Reception of Early Ibadi Theology A Commentary on the "Book on Monotheism" by 'Abd Allāh b. Yazīd al-Fazārī (2nd/8th Century) - Salimi, Abdulrahman al- (Harrassowitz Verlag, 2021)
‘Abd Allāh b. Yazīd al-Fazārī (2nd/8th century) was one of the leading early Islamic theologians. His works are still among the most reliable and accessible to scholars and this text is a significant new addition to al Fazari’s texts that were previously published (IHC. 104/IHC. 182). This present study is based on a discussion of al-Fazārī’s teachings with the title Kitāb fī al-Tawḥīd, which is a commentary on his lost work by an anonymous North African Ibadi theologian and is unique because it is among the few known works which describe the doctrine of the early Ibadis. The addition of this text to al -Fazārī’s previously discovered writings provides us with further information about the early Ibadis’ theological views; more importantly, however, it also enables us to trace the development of the terminology they used and understand how and why it changed, as well as the intellectual aspects of the Islamic theological debates during the 2nd/8th century. This study successfully establishes that the opinions of this Ibadi school of theology have remained the same from one generation to the next - among the eastern Ibadis in Oman, Yemen and Hadhramawt as well as the western Ibadis in North Africa. It refutes previous speculation which maintained that al Fazārī’s views were on the decline in Ibadi circles from the middle of the 5th/11th century, since the evidence shows that the precise opposite was the case. In fact, this study shows that his theological teachings were still being followed in the 20th century by the Ibadis in Oman and North Africa.
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

Abū Ḥafṣ ʿUmar b. Jamīʿ - Salimi, Abdulrahman al- (Encyclopaedia of Islam, 2007)
Keywords: Biographies – Djerba

The Inter textual on early Islamic Sources between Kitāb al-Rudūd by al-Fazārī & Kitāb al-Taḥrīsh by Dirār b. ʿAmr al-Ghatafani - Salimi, Abdulrahman al- (2021)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle; Ġaṭāfānī; Ḍirār b. ʿAmr al-

Poetic Anthology of Ibāḍī Theology. Historical Readings of Ibn al-Naẓar’s al-Daʿāʾim and its Commentaries - Salimi, Abdulrahman al- (Der Islam, 2016)
Keywords: Poésie – Oman

The Collection of Ḥadīth in Early Islamic Iraq (2nd/8th Century): The Musnads Al-Rabī‘ b. Ḥabīb and Zayd ibn ‘Alī - Salimi, Abdulrahman al- (2018)
Keywords: Hadith – Exégèse

Makramid rule in Oman - Salimi, Abdulrahman al- (Proceedings of the Seminar for Arabian Studies, 2005)
The politico-economic involvement of Omani families in the Gulf region in the period of Makramid rule in Oman (385–442/995–1050) deserves further study. My research into this family has highlighted the political involvement of Oman in the interaction between the Gulf and Iran in this period. It also revealed another dimension, i.e. shipping through the Gulf and the use by Omani families of the old trade routes, starting from Soḥār, to Sīrāf and thence to al-Ābilah, and ending in Baṣrah. The trade network linking all these cities was mostly operated by the ships owned by Omani families and run by their employees. Although the Makramids dominated this trade, it should be noted that other Omani families were also involved in it. The weakness of Makramid rule was mainly due to the family's concentration on economic activities and its reluctance to become involved in military action. Consequently, they remained under Buyid authority throughout their rule in the coastal region of Oman. Yet we cannot deny that Mihiyār's praise of the Makramids for protecting and defending Oman referred to genuine actions on their part and was not simply empty compliments. Makramid rule defended coastal Oman effectively and extended into other parts of the country, especially under Abū ʾl-Qāsim and his son Abū ʾl-Jaysh. I conclude this paper with a table of the Makramid dynasty.
Keywords: Vie politique – Oman – 10e siècle

Al-ʿAlāqa bayna ‘l-A’imma wa’l-ʿUlamā’ wa-Taṭawwurāt al-Dawla al-ʿUmāniyya ḥattà Nihāyat al-Qarn 10/16. Qirā’a fī ‘l-Siyar al-ʿUmāniyya - Salimi, Abdulrahman al- (نزوى: مجلة فصلية ثقافية, 2002)
A study on the relationship between religion and the state in Oman, on the development of this relationship and its influence on political and social life in the region. An attempt to establish a connection between the historical texts (the Siyar, epistles) and to evaluate them as witnesses for explaining certain historical events.

The Nabhānīs: A Sketch for Understanding - Salimi, Abdulrahman al- (Studi Magrebini, 2020)
The Nabhānī State first appeared in Oman in the 6th/12th century and lasted till the 11th/17th century. During this period the fall of Baghdad, which occurred in 656/1258, led to a number of radical political and cultural changes in the Gulf region, and the aim of the present study is to re-evaluate the conclusions of the (2002) study against a wider background. In doing so it will firstly re-evaluate the original and modern sources dealing with that period. Secondly, it will take a broader look at the political and regional situation at that time and its impact on the course of Oman’s historical development – in other words, it will consider Omani history within a regional context. Thirdly, it will look for the roots of that state and relate it more accurately to Oman’s historical chronology and regional context.

Different succession chronologies of the Nabhānī dynasty in Oman - Salimi, Abdulrahman al- (Proceedings of the Seminar for Arabian Studies, 2002)
This paper examines the period from the 12th to the 17th centuries when Oman was ruled by the Nabhānī dynasty. Though the origin and history of this state remain largly obscure, some facts may be deduced from the historical records of Oman. Recent researchers have claimed that Omani historians have paid more attention to the influence of religion on Omani historical writing than to other important aspects of this dynasty's history. However, it should be noted that Omani chronicles hardly predate the 17th century, so even major events before that remain largely unrecorded, and Omani historians cannot be blamed for the consequent lack of documentation. This paper presents a new hypothesis on the origin of the Nabhānī dynasty, based on a re-examiniation of the various available sources such as fiqh, poetry and histories, and points out some of the pitfalls which await the unwary researcher in this field.
Keywords: Vie politique – Oman – 12e siècle

Early Islamic Theological Debates on Asmāʾ and Aḥkām: The Epistle of Khalaf b. Ziyād al-Baḥrānī - Salimi, Abdulrahman al- (Der Islam, 2026)
This study examines the theological debates surrounding the Ibāḍī epistle of Khalaf b. Ziyād al-Baḥrānī, written in the early 2nd/8th century. The epistle, which focuses on the theological concept of al-asmāʾ wa-l-aḥkām (names and rulings), represents one of the earliest known discussions of faith classifications and their legal implications in Islam. Khalaf’s work is compared to Kitāb al-Irjāʾ and the Epistle of Sālim ibn Dhakwān, highlighting how early Islamic sects, particularly the Ibāḍīs, Murjiʾites, and Muʿtazilites, debated the definitions of īmān (faith) and kufr (unbelief). The study situates Khalaf’s epistle within the broader theological discourse of the period, showing how his classification of faith-related rulings influenced later Ibāḍī thought. It also challenges the assumption that Ibāḍism only matured as a structured doctrine in the 6th/12th century, demonstrating its continuous evolution from the early Islamic period.

Inter-textual Unity in Quranic Hermeneutics: Naẓm/Munāsaba, al-Ǧišumī’s Philological Theory and Its Influence on Qurʾanic Exegesis - Salimi, Abdulrahman al- (Studi Magrebini, 2024)
The recent publication of a new edition of the Qurʾanic exegesis al-Tahḏīb fī ʾl-Tafsīr by al-Ḥākim al-Ǧišumī (d. 494/1101) highlights the topic of naẓm (coherence/consistency/order/ correspondence) as a subject essential to understanding the concept of iʿǧāz al-Qurʾān, the uniqueness of the Qurʾanic text, which is central to conceiving its early exegesis. The present article investigates al-Ǧišumī’s theory of naẓm in the Qur’ ān, while attempting to distinguish his theory from that of his contemporary al-Ǧurǧānī (d. 471/1074). In this article, we compile evidence of al-Ǧišumī’s novel philological theory and offer a broader historical evaluation of the concept of naẓm among Qurʾanic exegetes. Finally, this article examines for the first time how to take account of al-Ǧišumī’s methodology in our understanding of the conceptual structure of the Qurʾanic corpus. While the main focus of this article is on al-Ǧišumī’s approach to the theory of naẓm, it also considers the theory in a wider context. Moreover, although it touches on al-Ǧurǧānī’s views on naẓm, it does not discuss him in any detail, particularly since his ideas have already been examined extensively in numerous other books and academic papers.
Keywords: Coran – Commentaires

The New Silk Road and the Communication between the Middle East and China - Salimi, Abdulrahman al- (Krakowskie Studia Międzynarodowe, 2017)
Termin „Jedwabny Szlak” ma dwa znaczenia: dosłowne i metaforyczne. W czasach, kiedy termin ten został wprowadzony do obiegu, centrum handlowym ówczesnego globalnego świata był świat arabski. Później centrum to przesunęło się na zachód, w dużym stopniu ze względu na chaos i zaburzenia, które zaczęły wstrząsać Bliskim Wschodem. W kolejnym okresie handel światowy zaczął intensywnie rozwijać się na Dalekim Wschodzie, z którym ściśle powiązana jest Zatoka Arabska/ Perska oraz basen Morza Czerwonego. Dzisiaj gospodarcze znaczenie Jedwabnego Szlaku staje się ważniejsze niż kiedykolwiek. W artykule analizowane są kulturowe aspekty idei Jedwabnego Szlaku oraz formy, w jakich ta idea zaczyna się wyrażać.

Trends in Religious Reform on the Arabian Peninsula - Salimi, Abdulrahman al- (Hemispheres, 2012)
This article comparatively assesses the relationship of Arabian Peninsula governments to modern Islamic reform movements after the formation of nation-states by the British Government in post-Ottoman Arabia. Over the last half century the region of the Arabian Peninsula has experienced an Islamic awakening that has played an integral role in the process of modernization in Arabian states. There are three aims of this study: 1) to examine the influence of the traditional Islamic schools of theology on re-shaping the identities of Arabian states. 2) to explore the degree to which the governments of the nation states and the prior political establishments informed the contemporary vision of religious reform 3) to consider the impact that the recent wealth of Arabian States, especially the wealth of the GCC countries, has had on the creation of the modern Islamic revival since the discovery of oil. [PUBLICATION ABSTRACT]

The Influence of Ibāḍī siyar on the Orientalists’ Understanding of the Formation of Islam - Salimi, Abdulrahman al- (2017)
Keywords: Orientalisme – Ibadisme

Reconstructing Early Ibāḍī Theology in North Africa: The influence of ʿAbdallāh b. Yazīd al-Fazārī - Salimi, Abdulrahman al- (Studia Islamica, 2021)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle; Malshūṭī; Tibghūrīn b. ʿĪsā al-

The Influence of Ibadi Siyar Manuscripts on the Orientalists'' Understanding of the History of Early Islamic Theology - Salimi, Abdulrahman al- (Manuscripta Orientalia, 2017)
The article is devoted to the achievements and approaches of specialists, mostly American, British, German, French and Italian in the analysis of Ibadi siyar and the new perspectives of the research connected with the analysis of the MSS material. The general tendency in the field now is to follow the footsteps of Van Ess, Madelung and Cook, and rather than developing new theories and hypotheses, to seek out and identify well documented texts that will offer a reliable picture of Islamic thought before the 3rd/9th century. To provide a clearer general context, the texts could also be rearranged in historical order and grouped on the basis of the ideas they present. Most works produced by the different Ibadi groups during the early period are not representative of particular literary genre. However, we do not have precise data on the Islamic material on ‘ilm al-kalam that has been discovered so far from the period up to the end of the 3rd/9th century. Because of the importance attached to siyar by Ibadi ‘ulama’ during the 10th/16th and 11th/17th centuries Ibabi schools began to seek out their roots and collect early manuscripts and works of literature on the Ibadi legacy... The article is devoted to the achievements and approaches of specialists, mostly American, British, German, French and Italian in the analysis of Ibadi siyar and the new perspectives of the research connected with the analysis of the MSS material. The general tendency in the field now is to follow the footsteps of Van Ess, Madelung and Cook, and rather than developing new theories and hypotheses, to seek out and identify well documented texts that will offer a reliable picture of Islamic thought before the 3rd/9th century. To provide a clearer general context, the texts could also be rearranged in historical order and grouped on the basis of the ideas they present. Most works produced by the different Ibadi groups during the early period are not representative of particular literary genre. However, we do not have precise data on the Islamic material on ‘ilm al-kalam that has been discovered so far from the period up to the end of the 3rd/9th century. Because of the importance attached to siyar by Ibadi ‘ulama’ during the 10th/16th and 11th/17th centuries Ibabi schools began to seek out their roots and collect early manuscripts and works of literature on the Ibadi legacy. The latter were copied and preserved per se without diluting them or considering them in the context of the other Islamic schools. That is why the Ibadi school was able to remain united and steadfast in the face of the contemporary modernization movements which continue to this day. Most of the compilations of the texts that are currently in our possession comprise not more than ten volumes in all. Scholars and copyists have rearranged each of these manuscripts, so that each copy has a different number and sequence of siyar texts. The existing text formats raise the important question of whether Ibabi siyar are actually a literary genre. Until now nobody has really studied siyar in such a way that their specific genre characteristics have been defined in detail.

Regulating the Sea: A 9th Century Ibadi Manuscript on Maritime Law - Salimi, Abdulrahman al- (2018)

Reconstructing Ibāḍī Theology in North Africa: the influence of ʿAbdallāh ibn Yazīd al-Fazārī - Salimi, Abdulrahman al- (2019)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

Identifying the (Ibadi/Omani) Siyar - Salimi, Abdulrahman al- (Journal of Semitic Studies, 2010)
Keywords: Prosopographie – Oman

The Religious Policies in Oman: Renewal in the Modern State - Salimi, Abdulrahman al- (Oman, Ibadism and modernity, 2018)

From the First Renaissance to the Second: The Historical and Legal Basis for the Sultanate - Salimi, Abdulrahman al- (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Shurūḥāt al-Daʿā’im li-Ibn al-Naḍr min Wujhat Naẓr Tārīkhiyya - Salimi, Abdulrahman al- (Qirā’āt fī Fikr Aḥmad b. Sulaymān b. al-Naḍr al-Samā’ilī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Yawmay 27-28 Muḥarram 1424 al-muwāfiq 30-31 Māris 2003, 2006)

Ibadi Studies and Orientalism - Salimi, Abdulrahman al- (On Ibadism, 2014)
Keywords: Orientalisme – Ibadisme

Oman: a maritime history - Salimi, Abdulrahman al-; Staples, Eric (Georg Olms Verlag, 2017)
Keywords: Navigation – Oman

The Political Organization of Oman from the Second Imamate Period to the Yaʻrūba: Rereading Omani Internal Sources - Salimi, Abdulrahman al- (L’ibadisme dans les sociétés de l’Islam médiéval, 2018)

A maritime lexicon: Arabic nautical terminology in the Indian ocean: English-Arabic edition - Salimi, Abdulrahman al-; Staples, Eric (Georg Olms Verlag, 2019)
Keywords: Navigation – Oman

Ibāḍism and the Creation of the Qur’ān - Salimi, Abdulrahman al- (Ibadi theology: rereading sources and scholarly works, 2015)

Reflections of a Muslim-Portuguese maritime world in a sixteenth-century Portuguese source - Salimi, Abdulrahman al-; Staples, Eric (Proceedings of the Seminar for Arabian Studies, 2015)
This paper discusses a record of expenses of an early sixteenth-century Portuguese vessel, the Santa Maria do Monte, during its voyage from Goa to Hormuz and back in 1520-1521, stopping in the Omani ports of Qalhāt, Ṭīwī, Qurayyāt, Muscat (Masqat), and Khawr Fakkān along the way. The route sailed during this voyage is examined in light of regional navigational practices, and the composition of the crew is discussed, emphasizing the significant non-Portuguese population on board. The nature of the ship and the specific costs of maintaining this vessel during the voyage are also addressed. Collectively, the cultural intersections involved with the navigation, the crew, and the maintenance regime of this vessel provide specific examples of maritime relationships in the region. In terms of its broader significance, such evidence of a high concentration of regional actors in a Portuguese instrument of maritime power alludes to a more complex and interdependent relationship between the Portuguese and the Arabian Sea maritime spheres. It also highlights a specific segment of the vibrant maritime Indian Ocean mosaic that the Portuguese were compelled to navigate during their imperial endeavours.
Keywords: Relations – Oman – Portugal

The Ibadis in the region of the Indian Ocean. Sect. 1: East Africa - Gaube, Heinz (Georg Olms Verlag, 2013)
Keywords: Ibadisme – Afrique de l'Est

The ports of Oman - Salimi, Abdulrahman al-; Staples, Eric (Georg Olms Verlag, 2017)

Ibāḍī texts from the 2nd/8th century - Salimi, Abdulrahman al-; Madelung, Wilferd (Brill, 2018)
In 'Ibāḍī Texts from the 2nd/8th Century' Abdulrahman Al-Salimi and Wilferd Madelung present an edition of fourteen 'Ibāḍī' religious texts and explain their contents and extraordinary source value for the early history of Islam. The 'Ibāḍīs' constitutes the moderate wing of the Kharijite opposition movement to the Umayyad and ʿAbbasid caliphates. The texts edited are mostly polemical letters to opponents or exhortatory to followers by ʿAbd Allah b. Ibāḍ, Abu l-ʿUbayda Muslim b. Abi Karima and other Ibāḍī leaders in Basra, Oman and Hadramawt. An epistle detailing the offences of the caliph ʿUthman is by the early Kufan historiographer al-Haytham b. ʿAdi. By their early date and independence of the mainstream historical tradition these txts offer the modern historian of Islam an invaluable complement to the well-known literary sources
Keywords: Sources – Ibadisme

Illuminated Qurans from Oman - Gaube, Heinz; Salimi, Abdulrahman al- (Georg Olms Verlag, 2016)
This book is a first attempt to present Omani Quranic manuscripts and their illuminations to a wider public and to discuss their originality in the wider context of Quranic manuscripts, Islamic art as a whole and beyond that in the wider context of Oriental art in general. This book focuses on the most prominent components of Quran illuminations, the frontispieces. The organization of the material starts with the most unpretentiously designed, plain frontispieces without frames and without horizontally subdivided pages and ends with one-page or double-page frontispieces with illuminations in two well-defined different styles which can be subdivided into several under groups. The first of these styles is named "Omani" and the second "Persian influenced" The first style is characterized by primarily geometric ornaments whereas vegetal forms and sophisticated designs distinguish the second. The origin of the second style can be easily traced back to Iran, most probably Southern Iran and there to the school of Shiraz. This style is closely related to the art of India Quran illuminations which doubtlessly had influenced Omani Quran illuminations too. The question of the origins of the fascinating first style, which has no equals in the Islamic world, can be answered in different ways and will be discussed in a separate subchapter
Keywords: Manuscrits – Oman

Al-Salimi, Abdulrahman: On the Reception of Early Ibadi Theology. A Commentary on the Book on Monotheism by ‘Abd Allāh b. Yazīd al-Fazārī (2nd/8th Century). - Metzler, Berenike (Orientalistische Literaturzeitung, 2022)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Recension

Portugal in the sea of Oman: religion and politics: research on documents - Salimi, Abdulrahman al-; Jansen, Michael (von Zabern, 2012)
Keywords: Relations – Oman – Portugal

Early Islamic Law in Basra in the 2nd/8th Century. Aqwāl Qatāda b. Diʿāma al-Sadūsī, edited by Al-Salimi, Abdulrahman - Francesca, Ersilia (Studi Magrebini, 2020)
Keywords: Recension

Biographical Dictionaries in Oman - Salimi, Abdulrahman al- (Today's perspectives on Ibadi history, 2017)
Keywords: Biographies – Oman

Sultan Qaboos and modern Oman, 1970-2020 - Fromherz, Allen James; Salimi, Abdulrahman al- (Edinburgh University Press, 2022)
This is the first, timely account of the modern Oman over the entire reign of Sultan Qaboos (1970-2020). The book provides unique, wide-ranging interdisciplinary and international perspectives on modern Oman by specialists in a variety of fields from Oman, Europe and North America. Utilising a range of perspectives, all chapters connect to the theme of rebirth, of the connections between the past and the future pursued by Sultan Qaboos and his government in fields as diverse as health, religion, law, economy, heritage and diplomacy. Not overlooking the many challenges faced during Sultan Qaboos' reign and still faced by Oman, the book engages various theories and perspectives about Oman's economic, religious, educational and cultural transformations under Qaboos (d. 2020 CE)
Keywords: Vie politique – Oman – 1970-2020

Muslims, Scholars, Soldiers: The Origin and Elaboration of the Ibadi Imamate Traditions * By ADAM GAISER. - Salimi, Abdulrahman al- (Journal of Islamic Studies, 2013)
Keywords: Recension

سلسلة الدراسات الإباضية والعمانية المجلد الثاني: كتاب عمان وما وراء البحار - بنت ناصر, فاطمة (شباب التفاهم, 2018)
Keywords: Recension

On the Emergence of Al-Bū Saʿīd Dynasty: Perspectives from an Unfinished and Anonymous Manuscript, Mirʾāt Aḥwāl ʿaṣr Al-Ǧadīd Fī Sīrat Al-Sulṭān Ḥamad B. Ṯūwaynī B. Saʿīd - Limbert, Mandana E.; Salimi, Abdulrahman al- (Nouvelles Chroniques du Manuscrit au Yémen, 2024)
Keywords: Vie politique – Zanzibar – 1893-1896

The Essentials of Ibāḍī Islam, by Valerie J. Hoffman - Salimi, Abdulrahman al- (Ilahiyat studies, 2013)
Keywords: Recension

Banians of Muscat: a South Asian merchant community in Oman and the Gulf, c. 1500-1700 - Salimi, Abdulrahman al- (The Gulf in World History: Arabian, Persian and Global Connections, 2020)

Early Islamic Law in Basra in the 2nd/8th Century. Aqwāl Qatāda b. Diʿāma al-Sadūsī, written by Abdulrahman al-Salimi - Benkheira, Mohammed Hocine (Studia Islamica, 2020)
Keywords: Recension

The Sirah of Imam Râshid b. Sa'id to the People of Mansürah - اليحمدي, راشد بن سعيد (Ibāḍism East of Mesopotamia: Early Islamic Iran, Central Asia and India, 2016)
Keywords: Ibadisme – Asie centrale

The Omani Renaissance: Renewal of Fiqh and Religious Reform - Sayyid, Ridwan al- (Oman, Ibadism and modernity, 2018)
Keywords: Fiqh

Majlis al-Shura in Oman - Salimi, Hussain S. al- (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)
Keywords: Vie politique – Oman – 1970-2020

The southern Batinah ports - Jawhari, Nasser Said al- (The ports of Oman, 2017)

The Iftāʾ Office of Oman: Its Objectives and Policy - Sulaimi, Abdullah Ahmed al- (Oman, Ibadism and modernity, 2018)

Constitutional Reforms During the Reign of Sultan Qaboos - Kharusi, Salim al- (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Dirāsa li-Kitābat Qawāmīs al-Biyūghrāfiyā fī ʿUmān - Salimi, Abdulrahman al- (Aʿmāl al-Multaqà al-ʿIlmi al-awwal ḥawla Turāth Salṭanat ʿUmān al-Shaqīqa Qadīman wa-Ḥadīthan, 2003)

The Development in the Ibāḍī Theology during the 18th and 19th Centuries - Busaidi, Saleh Ahmed al- (Oman, Ibadism and modernity, 2018)

O[ma]n Ibadism and Modernity - Rebstock, Ulrich (Die Welt des Islams, 2020)
"O[ma]n Ibadism and Modernity" published on 27 May 2020 by Brill.
Keywords: Recension

Oman and Islamic maritime networks (632-1507 CE) - Staples, Eric (Oman: a maritime history, 2017)
Keywords: Navigation – Oman

Abdulrahman Al-Salimi and Eric Staples, eds., Oman: A Maritime History. Studies on Ibadism and Oman , vol. 9, Hildesheim: Georg Olms Verlag, 2017. - Bahl, Christopher (Der Islam, 2023)
Keywords: Recension

Jumuiya ya Kiislamu ya Istiqaama Tanzania and Modern Ibāḍism in East Africa, 1985–2016 - Mathews, Nathaniel (Oman, Ibadism and modernity, 2018)
Keywords: Zanzibar

Portugal in the Sea of Oman. Religion and Politics. Research on Documents, edited by Abdulrahman Al-Salimi and Michael Jansen and in collabaration with Pedro Pinto, Karsten Ley, and Helmut Siepmann - Biedermann, Zoltán (Journal of Early Modern History, 2021)
Keywords: Recension

Muscat and Mutrah - Gaube, Heinz (The ports of Oman, 2017)

Le grand réformateur Shaykh Bayyūḍ tel que je l’ai connu Ibrāhīm b. ʿUmar, 1313–1401/1899–1981: un témoignage - Jaabiri, Farhat (Oman, Ibadism and modernity, 2018)
فرحات بن علي الجعبيري
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab

The port of Gwadar and its relationship with Oman - Nicolini, Beatrice (The ports of Oman, 2017)

The development of boatbuilding technologies and typologies - Vosmer, Tom (Oman: a maritime history, 2017)
Keywords: Archéologie – Oman

Al-Salimi, Abdulrahman / Madelung, Wilferd: Early Ibāḍī Literature. 2011. - Rebstock, Ulrich (Orientalistische Literaturzeitung, 2017)
Keywords: Recension

Oman’s maritime activities throughout the Indian Ocean 1650-1856 CE - Nicolini, Beatrice (Oman: a maritime history, 2017)
Keywords: Navigation – Oman

Regulating Seafaring in Early Islamic Jurisprudence: A 3rd/9th Century Ibāḍī Manuscript on Maritime Law - Salimi, Abdulrahman al- (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)

Review: A Maritime Lexicon Arabic Nautical Terminology in the Indian Ocean - Acevedo, Juan (Rutter Book Review, 2020)
Keywords: Recension

Julfar and the ports of northern Oman - Power, Timothy (The ports of Oman, 2017)

Review of Early Ibāḍī Literature. Abu l-Mundhir Bashīr b. Muḥammad b. Maḥbūb. Kitāb al-Raṣf fi l-Tawḥīd, Kitāb al-Muḥāraba and Sīra. (Abhandlungen für die Kunde des Morgenlandes, 75) - Prevost, Virginie (Wiener Zeitschrift für die Kunde des Morgenlandes, 2012)
Keywords: Recension

Ibāḍī Policy on Education and Learning in the Premodern Period - Kondo, Yohei (Oman, Ibadism and modernity, 2018)
Keywords: Enseignement – Oman

The Critique of Ḥadīth in Early Ibāḍī Literature - Salimi, Abdulrahman al- (Local and global Ibadi identities, 2019)

Religion and Politics in Ibāḍism: A Historical Survey - Madelung, Wilferd (Oman, Ibadism and modernity, 2018)

Navigation in Islamic sources - Staples, Eric (Oman: a maritime history, 2017)
Keywords: Navigation – Oman

Ports in the Indian Ocean - Pearson, Michael (The ports of Oman, 2017)

Conclusion: the ports of Oman today - Staples, Eric (The ports of Oman, 2017)

East Africa and Oman, c. 600-1856 CE - Horton, Mark (The ports of Oman, 2017)
Keywords: Relations – Oman – Afrique de l'Est

New Materials on Ibāḍism in Iraq and Arabia at the Second and Third Centuries of Islam. Review of Al Salimi & Madelung, Ibāḍī Texts from the 2nd/8th Century (Leiden: Brill, 2018); Al Salimi, Ibadi Texts in Oman from the 3rd/9th Century (Leiden: Brill, 2021) - Baptiste, Enki (Al-ʿuṣūr al-wusṭa, The Bulletin of Middle East Medievalists, 2024)
Keywords: Recension

The Notion of Jesus’ Return in the Views of Two Ibāḍī Scholars: Muḥammad Aṭfayyish and Aḥmad al-Khalīlī - Albayrak, Ismail (Oman, Ibadism and modernity, 2018)
Keywords: Atfiyyash; Muhammad b. Yusuf (1821-1914); Coran – Commentaires – 19e siècle; Coran – Commentaires – 20e siècle

Modern Oman: studies on politics, economy, environment and culture of the Sultanate - Kapiszewski, Andrzej; Salimi, Abdulrahman al-; Pikulski, Andrzej (Księgarnia Akademicka, 2006)
Keywords: Vie politique – Oman – 1970-2020

Hinterland trade and maritime networks in Oman from Iron Age to Late Antiquity (1000 BCE-630 CE) - Reddy, Anjana (Oman: a maritime history, 2017)
Keywords: Archéologie – Oman

Abdulrahman al-Salimi / Heinz Gaube (eds.): A New Collection Dedicated to Ibadism and Oman: A Review of the First Four Publications (2013–4) - Aillet, Cyrille (Der Islam, 2015)
Keywords: Recension

Early Ibāḍī Theology : Six kalām texts by ʿAbd Allāh b. Yazīd al-Fazārī, written by Abdulrahman al-Salimi and Wilferd Madelung - Aillet, Cyrille (Arabica, 2017)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Recension

Was There an Arab Intellectual Revival (Nahḍa) in the 17th and 18th Centuries? A Review Essay - Lange, Christian (Oman, Ibadism and modernity, 2018)

Redefining Ibāḍī Identity through Religious Discourse in the Time of the Nahḍa - Ziaka, Angeliki (Oman, Ibadism and modernity, 2018)
Keywords: Réformisme

Early Ibadi Theology: New Material on Rational Thought in Islam from the Pen of al-Fazārī (2nd/8th Century) - Fazārī, ʿAbd Allāh ibn Yazīd (Brill, 2021)
1 The Book of Rebuttals / كتاب الردود 2 The Epistle to Abū Qudāma and Abū Khālid / كتاب إلى أبي قدامة وأبي خالد 3 The Book of Legal Opinions كتاب الفتيا / 4 The Book of Monotheism on the Knowledge of God / كتاب التوحيد في معرفة الله 5 The Book of Divine Expressions / كتاب العبارات الإلهية 6. The Book about Matters on Which Ignorance Is Permissible and Matters on Which Ignorance Is Impermissible / كتاب ما يسع جهله وما لا يسع جهله 7 The Book on the Categories and Regulations كتاب الأسماء والأحكام
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

Omani State Policies Concerning Buddhist Expatriates: Their Effects and Significance for the Sri Lankan Theravāda Community in Muscat - Wrona, Alexander (Oman, Ibadism and modernity, 2018)

Omani-Portuguese maritime activities (1500-1650 CE) - Floor, Willem (Oman: a maritime history, 2017)
Keywords: Relations – Oman – Portugal

Qalhat and Sur - Vosmer, Tom (The ports of Oman, 2017)
Keywords: Archéologie – Oman

Generic Islam? Official Religious Discourse in the Sultanate of Oman - Broucek, James (Oman, Ibadism and modernity, 2018)

Ijtihād and the Ibāḍī Reform Movement in North Africa: Shaykh Muḥammad Aṭfayyish’s ‘Re’-Interpretation of Kitāb al-Nīl - Francesca, Ersilia (Oman, Ibadism and modernity, 2018)
Keywords: Atfiyyash; Muhammad b. Yusuf (1821-1914); Réformisme – Mzab

Maritime trade in the Bronze Age - Vosmer, Tom (Oman: a maritime history, 2017)
Keywords: Archéologie – Oman

The ancient port of Sumhuran - Avanzini, Alessandra (The ports of Oman, 2017)
Keywords: Archéologie – Oman

Islamic Modernisms: An Ibāḍī-Shīʿite Perspective - Modaressi, Hossein (Oman, Ibadism and modernity, 2018)
Keywords: Réformisme

Review of Early Ibāḍī Theology. Six kalām texts by ʿAbd Allāh b. Yazīd al-Fazārī. (Islamic History and Civilization 106) - Thiele, Jan (Wiener Zeitschrift für die Kunde des Morgenlandes, 2016)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Recension

Islamic art in Oman - Salimi, Abdulrahman al-; Gaube, Heinz; Korn, Lorenz (Mazoon printing, publishing & advertising, 2014)
Keywords: Arts – Oman

Religious Tolerance in Oman and Ibāḍī Islam - Propst, Amanda (Oman, Ibadism and modernity, 2018)
Keywords: Tolérance religieuse – Oman

Sohar: forelands, Umland and Hinterland in the history of an Omani entrepôt - Averbuch, Brian (The ports of Oman, 2017)
Keywords: Navigation – Oman

Religion and Politics in Contemporary Omani Ibāḍism - Francesca, Ersilia (Oman, Ibadism and modernity, 2018)

Reviewed Work: The Ports of Oman by Abdulrahman Al Salimi/Erich Staples - Hoffmann-Ruf, Michaela (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 2020)
Keywords: Recension

Abdulrahman Al-Salimi and Wilferd Madelung (eds): Ibāḍī Texts from the 2nd/8th Century. (Islamic History and Civilization. Studies and Texts 133.) vi, 392 pp. Leiden: Brill. 2018. €110. ISBN 978 90 04 33064 1. - Gaiser, Adam R. (Bulletin of the School of Oriental and African Studies, 2018)
Keywords: Recension

Hormuz: Bandar and Mulk (port and dominion): eleventh to early sixteenth century CE. When Hormuz was the hinge of a new land and maritime system, and Oman was its pivot: the Hormuz - Oman - Kij mercantile dominion - Piacentini Fiorani, Valeria (The ports of Oman, 2017)

“Friend to All, Enemy to None”: Oman’s Quiet Diplomacy Since 1970 - Owtram, Francis (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Politique étrangère – Oman – 1970-2020

Review of The Ports of Oman - Hoffmann-Ruf, Michaela (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 2020)
Keywords: Recension

The Individual Reaction to Western Modernization - Ghazal, Amal N. (Oman, Ibadism and modernity, 2018)
Keywords: Réformisme

Ibāḍīs in the Cultural Memory of Modern Ḥaḍramawt - Rodionov, Mikhail A. (Oman, Ibadism and modernity, 2018)

Maritime history, world history, global history: some thoughts on past, present and future - Alpers, Edward A. (Oman: a maritime history, 2017)
Keywords: Navigation – Oman

The South East European View - Ziaka, Angeliki (Oman and overseas, 2013)

AL-SALIMI, A., and W. MADELUNG (eds.) — Early Ibadi Literature. Abu l-Mundhir Bashir b. Muhammad b. Mahbub, Kitab al-Rasf fi l-Tawhid, Kitab al-Muharaba and Sira - Custers, Martin H. (Bibliotheca Orientalis, 2012)
Keywords: Recension

Ibāḍism and State Formation in Oman - Wilkinson, John Craven (Oman, Ibadism and modernity, 2018)

AL SALIMI, A., and E. STAPLES (eds.) – Oman. A Maritime History - Custers, Martin H. (Bibliotheca Orientalis, 2018)
Keywords: Recension

The Heritage of Ibāḍism in the Medieval History of Ḥaḍramawt in the Context of the Ideological Struggle between the Irshādites and the ʿAlawites - Frantsouzoff, Serge A. (Oman, Ibadism and modernity, 2018)

From Colonial Documentation to Citizenship Boundaries: Marriage Policy across Two Nahḍas - Limbert, Mandana E. (Oman, Ibadism and modernity, 2018)

Early Islamic Theological Influence in Jurisprudence. An Ibāḍī Perspective - Salimi, Abdulrahman al- (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Fiqh – Ibadisme

Public Health and the Omani Renaissance - Foley, Sean (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

AL SALIMI, A., and E. STAPLES (eds.) – The Ports of Oman - Custers, Martin H. (Bibliotheca Orientalis, 2018)
Keywords: Recension

Ibāḍism and the Tradition of Tolerance in Oman - Sheline, Annelle R. (Oman, Ibadism and modernity, 2018)
Keywords: Tolérance religieuse – Oman

Ibāḍī-Omani Creeds and the Construction of Omani Religious Discourse - Hoffman, Valerie J. (Oman, Ibadism and modernity, 2018)

Oman and Ibadism in Modern French Historiography: Assessing a Semi-Failure - Dridi, Moez (Oman and overseas, 2013)

Book review: Oman and Overseas éd. Michaela Hoffmann-Ruf et Abdulrahman al-Salimi, written by Oman and Overseas - Prevost, Virginie (Arabica, 2015)
"Book review: Oman and Overseas éd. Michaela Hoffmann-Ruf et Abdulrahman al-Salimi, written by Oman and Overseas" published on 04 Mar 2015 by Brill.
Keywords: Recension

Omani Peacemaking and Middle East Crises in the 2010s: Sultan Qaboos’ Last Decade - Cole, Juan (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Politique étrangère – Oman – 1970-2020

Abdulrahman Al-Salimi and Eric Staples: A Maritime Lexicon: Arabic Nautical Terminology in the Indian Ocean. (Studies on Ibadism and Oman.) 641 pp. Hildesheim: Georg Olms Verlag, 2019. $98. ISBN 978 3 487 15393 3. - Bishara, Fahad Ahmad (Bulletin of the School of Oriental and African Studies, 2020)
Keywords: Recension

The Formation of Oman’s Maritime Power under the Yaariba and Sayyid Said - Staples, Eric (Oman and overseas, 2013)

Oman: The Russian View since the 15th Century - Rezvan, Efim (Oman and overseas, 2013)
Keywords: Récits de voyage – Oman

A Historic Perspective on the Nahḍa - Wilkinson, John Craven (Oman, Ibadism and modernity, 2018)
Keywords: Réformisme – Oman

Ibadis in East Africa: Archaeological and Historical Evidence - Horton, Mark (Oman and overseas, 2013)
Keywords: Archéologie – Zanzibar

Umani Ports in Chinese Sources - Kauz, Ralph (Oman and overseas, 2013)

Early Ibāḍī Literature: Abu l-Mundhir Bashīr b. Muḥammad b. Maḥbūb Kitāb al-Raṣf fi l-Tawḥīd, Kitāb al-Muḥāraba and Sīra, by Abdulrahman al-Salimi and Wilferd Madelung (eds.) - Gaiser, Adam R. (Ilahiyat Studies, 2010)
Keywords: Recension

Beyond the Horizon and Back: The Sultan Qaboos Scholarship - Pritt, Jody (Sultan Qaboos and modern Oman, 1970-2020, 2022)

Religious Aspects in the Poetry of Abū Muslim al-Bahlānī - Michalak-Pikulska, Barbara (Oman, Ibadism and modernity, 2018)
Keywords: Littérature – Oman

Introduction: Sultan Qaboos, Omani Society, and the “Blessed Renaissance”, 1970–2020 - Fromherz, Allen (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

A Political Culture and Foreign Policy Shaped by a Moderate Religious View: The Case of the Sultanate of Oman - Rabi, Uzi (Oman and overseas, 2013)
Keywords: Vie politique – Oman – 1970-2020

The Roots of Religious Tolerance in the Omani-Ibāḍī Tradition - Gaiser, Adam R. (Oman, Ibadism and modernity, 2018)
Keywords: Tolérance religieuse – Oman

The Land of Frankincense: Dhofari Sites as National and World Heritage - Lewis, Krista (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Monuments – conservation – Oman

Al Salimi, Abdulrahman and Staples, Eric: A Maritime Lexicon. Arabic Nautical Terminology in the Indian Ocean. English-Arabic Edition. Hildesheim/Zürich/New York: Georg Olms Verlag 2019. 641 S. m. 341 Abb. 4° = Studies on Ibadism and Oman. Vol. 11. Hartb. € 88,00. ISBN 978-3-487-15393-3. - Müller, Walter W. (Orientalistische Literaturzeitung, 2020)
Keywords: Recension

Mosaic Oman: Views from India - Dietl, Gulshan (Oman and overseas, 2013)

Review of Oman. A Maritime History - Gemeinhardt-Buschhardt, Konstanze (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 2020)
Keywords: Recension

From Slumber to Assertion: Maritime Expansion of the Ibadis of Oman and the Responses of Estado da India,1622–1720 - Malekandathil, Pius (Oman and overseas, 2013)

MADELUNG, W., and A. AL-SALIMI (eds.) – Ibāḍī Texts from the 2nd/8th Century. (M.H. Custers) - Custers, Martin H. (Bibliotheca Orientalis, 2019)
Keywords: Recension

Omani Seafaring and Omani Boat - Vosmer, Tom (Oman and overseas, 2013)
Keywords: Archéologie – Oman

The British Historical View of Oman and Ibadism - Worrall, James (Oman and overseas, 2013)

Ibāḍīs in Zanzibar and the Nahḍa - Hoffman, Valerie J. (Oman, Ibadism and modernity, 2018)
Keywords: Zanzibar

The Legacy of Sultan Qaboos: A Historiographical Note - Rabi, Uzi (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Abdulrahman Al-Salimi and Wilferd Madelung: Early Ibāḍī Theology: Six kalām Texts by ‘Abd Allāh B. Yazīd Al-Fazārī. (islamic History and Civilization.) Cvi, 241 Pp. Leiden: Brill, 2014. €99. Isbn 978 90 04 27025 1. - Gaiser, Adam R. (Bulletin of the School of Oriental and African Studies, 2015)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Recension

Duqm and Salalah: Oman’s Ports and Special Economic Zones - Kinnier, Jeffrey (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Ports – Oman

The Portuguese in East Africa and the Omani Reconquest of East Africa - Newitt, Malyn (Oman and overseas, 2013)
Keywords: Relations – Oman – Portugal

The Tragedy of the Arab World - Ech-Cheikh, Mohammed (Oman, Ibadism and modernity, 2018)

Oman through Jewish Travellers’ Eyes - Schreiner, Stefan (Oman and overseas, 2013)
Keywords: Judaïsme – Oman; Récits de voyage – Oman

الإباضية في منطقة المحيط الهندي.. القسم الأول - شرق أفريقيا - بنت ناصر, فاطمة (شباب التفاهم, 2018)
Keywords: Recension

Religion and Political Structure: The Berber-Ibāḍī Perspective in North Africa between Diversity and Pluralism - Di Tolla, Anna Maria (Oman, Ibadism and modernity, 2018)
Keywords: Berbérisme – Afrique du Nord

Muscat and Sultan Qaboos: The Omanization of Muscat and the Muscatization of Oman - Guirado Alonso, Javier (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

The Seminar für Orientalische Sprachen (SOS) at Berlin: Aspects of the Relationship between Oman and Germany in the Late 19th and Early 20th Century - Hoffmann-Ruf, Michaela (Oman and overseas, 2013)
Keywords: Relations – Oman – Allemagne

HOFFMANN-RUF, M., und A. AL SALIMI (Hrsg.) – Oman and Overseas. proceedings of the Inter- national Conference ‘The Ibadism of Oman - Its Overseas Development and its perception Over- seas’ held at Tübingen University, 16th-19th of May 2011. - Custers, Martin H. (Bibliotheca Orientalis, 2014)
Keywords: Recension

Wood, Horses and Friendship. The Arabic Letters from Muscat to the Dutch in Kochi (1779) and Batavia (1798–1806) - Witkam, Jan Just (Oman and overseas, 2013)

In the Middle of a Reign - Hoffman, Valerie J. (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Prehistoric Interactions between Oman and the Indus Civilization: Projecting the Past in the Present - Kenoyer, Jonathan Mark (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Relations – Oman – Inde

Late pre-Islamic Oman: The Inner Evidence – The Outside View - Yule, Paul A. (Oman and overseas, 2013)
Keywords: Archéologie – Oman

The Main Languages of East Africa and their Literatures - Bakari, Mohammed Ali (Oman and overseas, 2013)
Keywords: Littérature – Zanzibar

Oman’s maritime history since 1856 CE - Allen, Jr, Calvin H. (Oman: a maritime history, 2017)
Keywords: Navigation – Oman

A Historical Survey of US-Omani Relations from 1790 to the Present - Leonard, Douglas R. (Oman and overseas, 2013)
Keywords: Relations – Oman – Etats-Unis

Omani Trade and Cultural Relations with East Asian Countries - Ziaee, Ali Akbar (Oman and overseas, 2013)
Keywords: Commerce – Oman

The Interpretation of Islam under Sultan Qaboos - Hoffman, Valerie J. (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Ibadisme – Oman

African Perspectives - Kusimba, Chapurukha M. (Oman and overseas, 2013)

Greening Oman: Islamic Environmentalism, Sustainable Development, and Post-Oil Futures - Curtis, Maria F. (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Développement durable – Oman

The Origins of Omani Identity - Wilkinson, John Craven (Oman and overseas, 2013)

Nation and State in Oman: The Initial Impact of 1970 - Peterson, John E. (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Literature in Oman During the Reign of Sultan Qaboos - Michalak-Pikulska, Barbara (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Littérature – Oman

The Growth of the Relationships between Oman, the Gulf and the Western Waters of the Indian Ocean. Oman: The Corner-Stone of a Maritime System - Piacentini Fiorani, Valeria (Oman and overseas, 2013)

Family in the Maghrib: The Case of Mzabi Society in the Nahḍa Period - Di Tolla, Anna Maria (Oman, Ibadism and modernity, 2018)

Ibāḍī Jurisprudence in Modern Context (International Perspectives) - Abou-el-Wafa, Ahmed (Oman, Ibadism and modernity, 2018)
Keywords: Fiqh; Fiqh – Ibadisme

Omani Seafaring Identity before the Early 1600s: Ethnic and Linguistic Diversity - Agius, Dionisius A. (Oman and overseas, 2013)
Keywords: Navigation – Oman

Ibāḍī Texts from the 2nd/8th Century - Love Jr, Paul M. (Al-Masāq, 2019)
Keywords: Recension

Danish and Norwegian Travel Accounts of Oman, 1765–1995: Changing Views across Sea and Land - Bang, Anne K. (Oman and overseas, 2013)
Keywords: Récits de voyage – Oman

Oman: The Arab Views - Ghazal, Amal N. (Oman and overseas, 2013)

The Christian and Hindu Communities in Oman (after 1970) - Howitz, Christopher J. R. (Oman, Ibadism and modernity, 2018)

Zanzibar: The Sultanate and the Ottoman State in Africa - Gol, Mohammed Z. (Oman and overseas, 2013)

Thamīnī, ʿAbd al-ʿAzīz al- - Calassanti Motylinski, Adolphe de; Lewicki, Tadeusz; Salimi, Abdulrahman al- (Encyclopaedia of Islam, 2010)
Keywords: Biographies – Mzab – 19e siècle

British travellers in Oman from 1627- to 1970 - Hajri, Hilal al- (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)
Keywords: Récits de voyage – Oman

The Swahili Coast: Africa’s Window on the Indian Ocean - Sheriff, Abdul Mohamed Hussein (Oman and overseas, 2013)

Coins of the Omani Imams during the Buyid Period: Studying the Bahla Hoard - Salimi, Abdulrahman al- (Die Grenzen der Welt: Arabica et Iranica ad honorem Heinz Gaube, 2008)
Keywords: Numismatique – Oman

Adopting to biodiversity conservation: the mobile pastoral Harasis tribe in Oman - Chatty, Dawn (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)

Historical Coincidences between Oman and Brazil: Portuguese Invaders, African Slaves and the Majlis al-Jinn - Pacheco, Leila M. S. (Oman and overseas, 2013)
Keywords: Esclavage – Oman

Broadening political participation in Oman. Basic facts - Kapiszewski, Andrzej (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)
Keywords: Vie politique – Oman – 1970-2020

Northern Indian Ocean Islamic seaports and the interior of the Arabian Peninusula - Zarins, Juris; Newton, Lynne (The ports of Oman, 2017)

Oman, Pakistan and Gwadur 1948-1958 - Hedigan, Christopher (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)

Oman and Omanis in Portuguese Sources in the Early Modern Period (ca. 1500-1750) - Cunha, João Teles e (Oman and overseas, 2013)
Keywords: Relations – Oman – Portugal

Population and workforce in Oman - Kapiszewski, Andrzej (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)

Early Ibāḍī Literature: Abu l-Mundhir Bashīr b. Muḥammad b. Maḥbūb Kitāb al-Raṣf fi l-Tawḥīd, Kitāb al-Muḥāraba and Sīra - Ibn Maḥbūb, Bashīr ibn Muḥammad (Harrassowitz Verlag, 2011)
Kitāb al-raṣf fī al-tawḥīd wa-aḥkām al-Qurʼān wa-al-asmāʼ wa-al-aḥkām wa-al-Sunnah wa-al-Imāmah wa-asmāʼ al-dār wa-aḥkāmuhā wa-ḥudūth al-ʻālam – Kitāb al-muḥārabah – Sīrat al-shaykh Bashīr ibn Muḥammad ibn Maḥbūb fī al-ḥadath al-wāqiʻ bi-ʻUmān
Keywords: Foi – Traité

Stamps as Messengers of the Renaissance: The Postal Issues of Oman During the Reign of Sultan Qaboos - Allen, Jr, Calvin H. (Sultan Qaboos and modern Oman, 1970-2020, 2022)

Oman under Qaboos: the emergence of a new diplomatic style in the Gulf - Rabi, Uzi (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)
Keywords: Vie politique – Oman – 1970-2020

Early Ibāḍī theology: six kalām texts - Fazārī, ʿAbd Allāh ibn Yazīd (Brill, 2014)
Kitab al-qadar (Book of predetermination) Kitab fi l-radd ʻala Ibn ʻUmayr (Book on refutation of Ibn ʻumayr) Kitab al-radd ʻala al-mujassima (Book of refutation of the Corporalists) Kitab al-futya (Book of legal opinion) Kitab al-tawḥid fi maʻrifat Allah (Book of monotheism in the recognition of God) Kitab fi man rajaʻa ʻan ʻilmih wa-faraqa al-Nabi wa-huwa ʻala dinih – (Book about whoever reneges on his knowledge and departs from the Prophet while remaining in his religion
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

Oman’s economic development - Pikulski, Andrzej (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)

His Majesty Sultan Qaboos as a Paradigm of Peace: Images in Foreign Writings and Media - Hajri, Hilal al-; Panagiotou, Nikolas S. (Oman, Ibadism and modernity, 2018)
Keywords: Vie politique – Oman – 1970-2020

The Development of Ibāḍī Jurisprudence Writing in Oman: al-Imām al-Sālimī as a Model - Shueili, Sulaiman bin Ali bin Amir al- (Oman, Ibadism and modernity, 2018)

Religious Education in General and Higher Education in Oman: Reality, Rationale, and Institutional Practices - Ḥusaynī, Sulaymān ibn Sālim ibn Nāṣir (Oman, Ibadism and modernity, 2018)

Shaykh al-ʿAmūd in Nishapur: al-Ḥākim al-Jishumī’s Lessons in the Jishum Mosque - Salimi, Abdulrahman al- (Teachers and Students, Reflections on Learning in Near and Middle Eastern Cultures: Collected Studies in Honour of Sebastian Günther, 2024)
Keywords: Enseignement – Iran

Contemporary poetry in Oman - Michalak-Pikulska, Barbara (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)
Keywords: Littérature – Oman

Islamic period Maritime trade and travel along the southern Arabian coasts of the Indian Ocean: the case of Socotra, the Hallaniyat, Masirah and Mabut islands - Zarins, Juris; Newton, Lynne S. (The ports of Oman, 2017)

Study groups, gender and the tradition of knowledge in Bahla - Limbert, Mandana E. (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)

The Sultanate of Oman: Geography, Religion and Culture - Salimi, Abdulrahman al-; Abbaspour, Mitra; Kelemen, Peter; Limbert, Mandana E. (2015)
The Cooper Union for the Advancement of Science and Art

The territorial divisions of Oman - Wilkinson, John Craven (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)
Keywords: Vie politique – Oman

Tolerance, Sincerity and Hospitality, as Experienced by European and American Travelers Visiting Oman in the 19th and 20th Centuries - Ḥusaynī, Sulaymān ibn Sālim ibn Nāṣir (Oman, Ibadism and modernity, 2018)
Keywords: Tolérance religieuse – Oman

The Multiple Legacies of Sultan Qaboos: Heritage and Omani Nation Building - Penzier-Hightower, Victoria; Worrall, James (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Documents from 1551-1827 Archivo General de Indias Arquivo Histórico de Moçambique Biblioteca Histórica de la Universidad Complutense de Madrid Biblioteca Nacional de España Instituto de Valencia de Don Juan Lily Library Real Academia de la Historia : Transcriptions, English translation, Arabic translation - Salimi, Abdulrahman al-; Jansen, Michael; Pinto, Pedro (Georg Olms Verlag, 2023)
Keywords: Relations – Oman – Portugal

Documents from 1817-1877 Arquivo Histórico Ultramarino : Transcriptions, English translation, Arabic translation - Salimi, Abdulrahman al-; Jansen, Michael; Pinto, Pedro (Georg Olms Verlag, 2023)
Keywords: Relations – Oman – Portugal

Documents from 1729-1817 Arquivo Histórico Ultramarino : Transcriptions, English translation, Arabic translation - Salimi, Abdulrahman al-; Jansen, Michael; Pinto, Pedro (Georg Olms Verlag, 2023)
Keywords: Relations – Oman – Portugal

Documents from 1611-1832 Biblioteca Nacional de Portugal (Supplement): Transcriptions, English translation, Arabic translation - Salimi, Abdulrahman al-; Jansen, Michael; Pinto, Pedro (Georg Olms Verlag, 2021)
Keywords: Relations – Oman – Portugal

Documents from 1548-1912 Arquivo Diplomático do Ministério dos Negócios Estrangeiros de Portugal Arquivo Distrital de Braga Arquivo Municipal de Cascais Arquivo dos Viscondes de Vila Nova de Cerveira Biblioteca da Faculdade de Direito de Lisboa Biblioteca Geral da Universidade de Coimbra Biblioteca Municipal de Elvas Colecção Pedro Pinto Museu Nacional de Arqueologia Sociedade de Geografia de Lisboa: Transcriptions, English translation, Arabic translation - Salimi, Abdulrahman al-; Jansen, Michael; Pinto, Pedro (Georg Olms Verlag, 2021)
Keywords: Relations – Oman – Portugal

Documents from 1551-1879 Archivo General de Indias Arquivo Histórico de Moçambique Biblioteca Histórica de la Universidad Complutense de Madrid Biblioteca Nacional de España Instituto de Valencia de Don Juan Lily Library Real Academia de la Historia : Transcriptions, English translation, Arabic translation - Salimi, Abdulrahman al-; Jansen, Michael; Pinto, Pedro (Georg Olms Verlag, 2023)
Keywords: Relations – Oman – Portugal